2018
DOI: 10.1080/09638288.2018.1468934
|View full text |Cite
|
Sign up to set email alerts
|

Ankle positions potentially facilitating greater maximal contraction of pelvic floor muscles: a systematic review and meta-analysis

Abstract: Pelvic floor muscle-training for women with urinary incontinence could be performed in standing with ankles in a neutral position or dorsiflexion to facilitate greater maximal pelvic floor muscle contraction. As urethral support requires resting contraction of pelvic floor muscles, decreased resting activity in plantar flexion identified in the meta-analysis indicates that high-heel wearers with urinary incontinence might potentially experience more leakage during exertion in a standing position. Implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The pelvis tilts anteriorly and the position of the sacrum opens the pelvic outlet, and both ischial tuberosities move away from each other, causing the PFMs to tighten [ 20 ]. Although ankle dorsiflexion is not directly related to the pelvic floor, it is thought to induce pelvic anterior tilting and increase the activation of the PFM [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pelvis tilts anteriorly and the position of the sacrum opens the pelvic outlet, and both ischial tuberosities move away from each other, causing the PFMs to tighten [ 20 ]. Although ankle dorsiflexion is not directly related to the pelvic floor, it is thought to induce pelvic anterior tilting and increase the activation of the PFM [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared the activation of PFMs during fixed posture of dorsiflexion and plantar flexion and reported that PFMs were activated in dorsiflexion and inactivated in plantar flexion [ 12 , 14 , 16 ]. Therefore, it was necessary to keep in mind the use of high heels in people with weak PFMs [ 15 ]. However, previous studies did not provide adequate information regarding ideal exercise posture to strengthen PFMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with urinary incontinence need to understand that physical posture during exercise and in daily life can affect urinary incontinence. Several studies have investigated the relationship between pelvic posture and PFM activation [79].…”
Section: Introductionmentioning
confidence: 99%